La couverture du crime par la presse : un portait fidèle ou déformé ? - Gabor, Thomas; Weimann, Gabriel (Criminologie, 1987)
The authors examined, through content analysis, some criticisms that have been levelled at the press in its coverage of crime. The propositions examined included the accusations that newspapers are preoccupied with violence and “street” crime, that they focus on the bizarre, are superficial in their reporting of crime, misinform the public about the characteristics of offenders and victims, and exhibit a conservative bias in their analysis. This study of a major Canadian daily newspaper revealed substantiation for some of these claims but failed to support others. Violent and street crimes received disproportionate coverage and very few articles contained an in-depth analysis of the roots of crime or the workings of the criminal justice system. The evidence was less clear or non-existent in relation to the claims that the press focus on nonroutine events, that they provide distorted images of offenders and victims and that they have a conservative bent. Commentant l'impact des masse-médias, Marshall McLuhan (1978) soulignait: To invade the private person, or to invade a group with teaching, with doctrines, with entertainment, all these are alike forms of violence. To assume the right to program the sensibilities or thoughts and fantasies of individuals or groups, has long been taken for granted as a viable form of personal or social action... Today, however, there is a new dimension in all of these activities. Electric media move information and people at the speed of light. It is this instant and total quality that constitutes the condition of mass man and the mass society (p. 212).